2014
DOI: 10.4088/jcp.13m08715
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention Following Trauma May Mitigate Genetic Risk for PTSD in Civilians

Abstract: Background Civilian posttraumatic stress disorder (PTSD) and combat PTSD are major public health concerns. Although a number of psychosocial risk factors have been identified related to PTSD risk, there are no accepted, robust biological predictors that identify who will develop PTSD or who will respond to early intervention following trauma. We wished to examine whether genetic risk for PTSD can be mitigated with an early intervention. Method 65 emergency department patients recruited in 2009–2010 at Grady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 58 publications
(37 reference statements)
1
54
0
1
Order By: Relevance
“…Most North Korean refugees stay in embassies of third countries for a short duration before entering South Korea [39] (p. 2). As numerous studies suggest the importance of early intensive interventions in PTSD [90,91], it is necessary to amend policies in which the Korean Embassy in the third countries would not only protect the refugees but would also offer expert crisis interventions to refugees exposed to traumatic events. In addition, there is a need to strengthen the quantitative and qualitative formal support systems provided after resettlement.…”
Section: Discussionmentioning
confidence: 99%
“…Most North Korean refugees stay in embassies of third countries for a short duration before entering South Korea [39] (p. 2). As numerous studies suggest the importance of early intensive interventions in PTSD [90,91], it is necessary to amend policies in which the Korean Embassy in the third countries would not only protect the refugees but would also offer expert crisis interventions to refugees exposed to traumatic events. In addition, there is a need to strengthen the quantitative and qualitative formal support systems provided after resettlement.…”
Section: Discussionmentioning
confidence: 99%
“…Results were divided according to the type of intervention (pharmacological or psychological). From the 29 articles reviewed, 16 reported significant effects of interventions for the prevention of PTSD or symptoms related to the disorder [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Of these, 22 studies used psychological interventions and 7 used pharmacological interventions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Four of the six studies that used CBT or related techniques reported results compatible with reduced occurrence of PTSD or PTSDrelated symptoms in groups who underwent interventions in relation to control groups 9,[17][18][19] . In the study by Mouthaan et al 24 , which did not report reductions in the occurrence of PTSD, the authors discuss the fact that one-fifth of the volunteers failed to adhere to the intervention program.…”
Section: Cognitive Behavioral Therapy (Cbt)mentioning
confidence: 98%
“…A fokozatos expozíciós terá-pia hatása a nemi erőszakot elszenvedett személyek esetében volt a legmarkánsabb. A szerzők a minta egy részén genetikai tesztelést is végeztek és azt találták, hogy a terápiás segítséget nem kapó kontrollcsoportban a magas genetikai rizikóval rendelkező személyek PTSD-szintje magasabb volt, mint az alacsony kockázatúaké, valamint, hogy a genetikai rizikó magasan korrelált a PTSD-tüne-tekkel a kontrollcsoportban, de nem a terápiás csoportban [57].…”
Section: Azonnali Pszichológiai Beavatkozások Traumatizáció Utánunclassified